Pendidikan Multikultural Sebagai Suatu Pendekatan Bagi Masyarakat Indonesia Heterogen dan Plural - Khofifah Indra Maya; Asnil Aidah Ritonga; Kartika Sari Putri; Fatma Ramadani Harahap; Wahyu Agung Daulay (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Indonesia is a country whose people have different customs related to different identities, races, communities and religions. So we want to teach multiculturalism, especially schools that respect existing differences, so that they don't become a source of quarrels and divisions. This mentality of shared resilience will create an everlasting dynamic, a social property that is a public personality that must be protected. In multicultural schooling, every progress and human culture is in an equal position without end. One of the important goals of the idea of a multicultural school is to help students acquire information and view other people with different identities, societies, and character values. Multicultural learning has four qualities, in particular: the value of equality, the value of resilience, the value of a sound-based system, and the value of pluralism. The qualities above seem to complement each other in responding to multiculturalism. As a result, multicultural schools are training that suppresses the most common ways to prohibit lifestyles that respect each other, earnestly, and whisper openness to social diversity that lives in the midst of general society with a high degree of majority.